(3JGQjN OhdI GdJQc aj Gdjefs - (3GHf GdegOj Hf GdgGOjs
(3ChdgG (B:s
(3MeOkG def LYd Cgd HjJ fHjg eMeO hHYO , abO SCdfi ef dG CMjO YeG CeQ hMJe Cf CLeY eGYedJg ef SjQI ehdGfG CejQ GdeDefjf GdefUhQ HGddg GdbGSe Hf eMeO Hf Ydi , hef bGe OGYjkG Edi Gddg ef ChdGOg GdCFeI s
(3BNQgG (B:s
(3hhbYJ MQhH bdjdI Hjf ChdGO GdEeGe GdbGSe Ydjg GdSdGe , hde JdHK GdaJfI Hjfge EdG jSjQkG , Ke YGOhG jOG Ydi ef YGOGge hSjCJi eaUdkG PcQ eG LQi HYO ehJ GdEeGe GdhGdO Ydjg GdSdGe ai SjQI GdEeGe GdeJhcd Ef TGA Gddg s
(3HgG fXGe GdJYbjHIs
(3eNJUQ ai SjQ CFeI Gdjef hMQhHge eY GdCJQGcs
(3hjHOC ef SfI (B986(3g` ef EeGeI GdfGUQ dOjf Gddg GdMSf Hf Ydi Hf OGhOs
(3Edi SfI (B1051(3g` hjJVef SjQI GdEeGe GdMSf Hf GdbGSe hMQhHg hZRhGJg hefGbHgs
(3dYddgG eShOI GdeDda s
(3HChdgG Jedc eDQN Sf s
Keywords: (3GdJGQjNs